Accelerated carbonation and structural transformation of blast furnace slag by mechanochemical alkali-activation. (June 2022) - Marple, Maxwell A.T.; Koroglu, Batikan; Morrison, Keith; Crowhurst, Jonathan; Balachandra, Anagi; Soroushian, Parviz; Mason, Harris E.
Abstract: Alternative cements and production routes are necessary to offset the considerable global CO2 emissions of Portland cement production. The combination of alkali-activation and mechanochemical milling in a CO2 rich atmosphere is a promising green direction for synthesizing cementitious material as it upcycles hazardous material (slag) while capturing wt% of CO2 during synthesis. We investigate the resulting structural transformations incurred during synthesis and hydration using a suite of characterization techniques including solid-state 27 Al, 29 Si, and 13 C NMR. The local aluminosilicate network structure of the processed clinker is best described by a melilite-type structure. Upon hydration, the network polymerizes to form a calcium, sodium aluminosilicate hydrate gel. The synthesis route also creates various metastable carbonates and bicarbonates from captured CO2 and alkali-additives that transform into stable carbonate phases like calcite, aragonite, and gaylussite, after hydration. This indicates accelerated carbonation reactions occur during clinker production and demonstrates novelty as a green cement technology.